O Primo Basílio e a relação espaço e tempo no audiovisual - Correia, Carlos Alberto [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This study aimed at understanding the space and time settings in the audiovisual narratives of O primo Basílio, who choose to mark the loyalty registration with the original work written by Eça de Queiroz. The main question refers to: in what extent is the reconfiguration of space and time of the original work in other media? The adaptations are concentrated in the audiovisual field, being the first produced for miniseries in Brazilian TV in 1988, and the second in film format completed and released in 2007. Both have Daniel Filho as diretor, the theoretical reference and the methodology adopted in this research allowed to point out the strategies launched between different media (film, television, literature) as regards the relationship between space and time in the fictional works of O primo Basílio. The conceptual foundations that guided this research are based from notes coming from literary, communication and cinema theories, represented by Benedito Nunes (1988; 1992), Paul Ricouer (1994), Roberto DaMatta (1997), Michel de Certeau (1998), Mikhail Bakthin (1997), Vanoye e Goliot-Leté (1994), Julie Sanders (2006), Linda Hutcheon (2013) and Robert Stam (2008). As a cut, we'll analyze the internal and external environments of the bourgeois house, the street, the space occupied by the theater in the narrative, the pre and post credits and opening of the audiovisual productions, as well as chronotopic role of the media: newspapers, magazines and television. This reading was done in an attempt to understand the space and time relations in the film and in the tv show as symbolic and many meanings which enabled them to both adaptations dialogue with the novel of Eça and its historical-social-cultural issues of the late portuguese nineteenth century, set for TV production (miniseries), and its reinterpretation in Brazil, São Paulo, in 1958, present in the film...

O presente trabalho tem como objetivo central compreender a configuração do espaço e do tempo nas narrativas audiovisuais de O primo Basílio, que optam por assinalar o registro de fidelidade à obra matriz escrita por Eça de Queirós. A pergunta principal refere-se à: em que medida ocorre a reconfiguração do espaço e do tempo da referida obra em outros suportes? As adaptações concentram-se no campo do audiovisual, sendo a primeira produzida para televisão em formato de minissérie em 1988, e a segunda em formato fílmico concluído e lançado em 2007. Ambas têm como diretor, Daniel Filho. O referencial teórico e a metodologia adotados nesta pesquisa permitiram assinalar para as estratégias lançadas entre diferentes mídias (cinema, televisão, literatura) no tocante às relações entre espaço e tempo ficcionais nas obras de O primo Basílio. As bases conceituais que nortearam esta investigação estão fundamentadas a partir de apontamentos oriundos da teoria literária, da comunicação e do cinema, representadas por Benedito Nunes (1988;1992), Paul Ricouer (1994), Roberto DaMatta (1997), Michel de Certeau (1998), Mikhail Bakthin (1997), Vanoye e Goliot-Leté (2011), Julie Sanders (2006), Linda Hutcheon (2013) e Robert Stam (2006; 2008). Como recorte, analisaremos os ambientes internos e externos da casa burguesa, a rua, o espaço ocupado pelo teatro na narrativa, os pré e pós créditos e abertura das produções audiovisuais, assim como a função cronotópica dos meios de comunicação: jornal, revista e televisão. Esta leitura se fez na tentativa de perceber as relações espaciotemporais no audiovisual como elementos simbólicos e plurissignificativos que permitiram para ambas as adaptações o diálogo com o romance de Eça e suas questões histórico-sociais-culturais do final do século XIX português, ambientado pela produção em minissérie, e sua releitura para o Brasil...
Keywords: Queiroz, Eça de 1845-1900; Literatura - Adaptações; Espaço e tempo na literatura; Literatura portuguesa; Cinema e literatura; Space and time in literature